Civil society stakeholder views on forensic DNA phenotyping: Balancing risks and benefits. (November 2019) - Samuel, Gabrielle; Prainsack, Barbara
Highlights: Forensic DNA phenotyping raises a range of regulatory, ethical and social issues. We interviewed thirty civil society stakeholders across nine EU countries to explore their perspectives with relation this. Views varied about how to balance various risks and benefits in terms of if, when and/or how the technology should be used. It was not a zero-sum game where risks to some goods detract from others. Each risk/benefit needed balancing against another. Abstract: Forensic DNA phenotyping (FDP) is an umbrella term for practices seeking to infer likely phenotypic characteristics based on crime scene DNA. Specifically, it is intended to help criminal investigators find an unknown suspected perpetrator by providing information about what the suspected perpetrator may look like based on the analysis of DNA left at the crime scene. While many purport the usefulness of FDP in this regard, its probabilistic nature, as well as its ability to disclose information about an individual that may be considered private raises a range of ethical and social concerns. This paper reports findings from interviews with thirty civil society stakeholders across nine European countries. Our findings reflect the wide variation of views in Europe regarding if, when and/or how the technology should be used in the criminal justice system, and we illustrate this by presenting the different ways in which our participants strike a balance between the potential usefulness of the technology, and the various ethical and social considerations.